Development of China's nature reserves over the past 60 years: An overview. (January 2019) - Huang, Yinzhou; Fu, Jiao; Wang, Wenrui; Li, Jing
Abstract: Establishing nature reserves (NRs) is the most important way to conserve biodiversity in China. In this paper, based on time series, we briefly reviewed its development history. The result showed that the pace and scale of the development of NRs have varied over time, and the development was highly related to China's economic and social development. Thus far, downsizing and downgrading still are the two major factors affecting the effectiveness of NRs. However, there are good signs showing that NRs of China will have a healthier future under the condition that environmental awareness both in the government and the public has been growing over the past decade. Then, suggestions on regulation, the participation of local communities, and environmental education are proposed accordingly.